Urinary Tract Infection in Nephrotic Syndrome - A study of 62 cases at Faridpur Medical College Hospital (Faridpur Medical College Journal, 2018)
Urinary tract infection is a common complication of Nephrotic syndrome, many cases remain asymptomatic. This study was aimed to determine the possible underlying causes of urinary tract infection in Nephrotic syndrome. The study population in this descriptive study included children aged six months to fourteen years old with Nephrotic syndrome referred to Paediatric ward of Faridpur Medical College Hospital from June 2015 to March 2016. The mean age was 6.12±3.25 years in UTI group and 7.26±3.39 years in without UTI group. Male were predominant in both groups, 15(60.0%) in UTI group and 24(64.9%) in without UTI group. Serum albumin, total protein, urinary protein excretion, the number of white blood cells, hemoglobin, erythrocyte sedimentation rate, blood creatinine, nitrogen, blood urea, serum triglycerides were not statistically significant between the groups. The most common microorganisms involved in urinary tract infection were: Escherichia coli (13%) & Klebsiella (13%). Majority 29(46.8%) patients had fever, 12(19.4%) had diarrhea, 11(17.7%) had bad smell of urine, 10(16.1%) had vomiting associated with diarrhea and 10(16.1%) had respiratory symptoms. Children with nephrotic syndrome are frequently predisposed to urinary tract infection and in most cases it is asymptomatic, often undiagnosed. E. coli is the commonest organism causing UTI.Faridpur Med. Coll. J. Jan 2018;13(1): 35-39